The effect of student dimension factors on online distance learning satisfaction: evidence from Indonesia / Ida Rosnidah ... [et al.] - -, Ida Rosnidah; Johari, Razana Juhaida; Siswoyo, Mukarto; Komara, Acep; -, Siti Nur Hadiyati (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Many universities and colleges were obliged to make quick changes to make online distance learning the default mode of education given the protracted lockdown period that followed COVID-19. During those times, higher education educators and learners were confronted with a sudden new norm of entirely tech-mediated teaching and learning. In addition to the benefits that online distance learning can provide to the new normal of teaching and learning, this transformation brings with it a number of problems. In pursuit of this, this study was undertaken among undergraduate students at Indonesian universities. The data was obtained via a web-based open-ended survey and analyzed using SEM - Partial Least Squares (PLS) software. According to the findings, only the student's computer anxiety influenced the student's satisfaction with online distance learning, but not the student's attitude. The findings of this study provide academic institutions with important insights into the aspects that could be employed to promote students' online distance learning satisfaction while also increasing retention and improving the quality of online teaching and learning. Limitations and future research directions are also highlighted.